Transformation of history learning methods in the digital era: Challenges and opportunities in schools - Firmansyah, Haris; Sastra Atmaja, Thomy (Indonesian Journal of Educational Development (IJED), 2025)
The rapid transformation of education in the digital era has created an urgent need to reexamine history teaching methods to ensure their relevance to the needs of today’s learners. This study aims to investigate the implementation of digital technology in history education in secondary schools in Pontianak, focusing on its impact on student engagement, the challenges encountered, and the opportunities that can be leveraged to enhance learning effectiveness. The research subjects consisted of history teachers and students from four public high schools, selected through purposive sampling based on their experience in integrating technology into history instruction. This research employed a qualitative phenomenological design, with data collected through in-depth interviews, classroom observations, and learning documentation. The findings indicate that the use of technologies such as documentary videos, historical simulations, and digital learning platforms enhances students' engagement with historical content, enabling them to learn more interactively and independently. Identified challenges include inadequate infrastructure, limited digital literacy, and unequal access to technological resources. Nevertheless, digital platforms and technologies such as virtual reality (VR) and augmented reality (AR) offer considerable opportunities to enrich historical learning experiences through their flexibility and immersive potential. The study recommends enhancing technological infrastructure, offering ongoing professional development for teachers, and implementing policies that promote equitable access to technology to optimize the digital transformation of history education.